Minimal clinically important difference in days at home up to 30 days after surgery. (19th November 2021) - Ferguson, M. T.; Kusre, S.; Myles, P. S.
Summary: Patient‐centred outcomes are increasingly recognised as crucial measures of healthcare quality. Days alive and at home up to 30 days after surgery (DAH30 ) is a validated and readily obtainable patient‐centred outcome measure that integrates much of the peri‐operative patient journey. However, the minimal difference in DAH30 that is clinically important to patients is unknown. We designed and administered a 28‐item survey to evaluate the minimal clinically important difference in DAH30 among adult patients undergoing inpatient surgery. Patients were approached pre‐operatively or within 2 days postoperatively. We did not study patients undergoing day surgery or nursing home residents. Patients ranked their opinions on the importance of discharge home using a Likert scale (from 1, not important at all to 6, extremely important) and the minimum number of extra days at home that would be meaningful using this scale. We recruited 104 patients; the survey was administered pre‐operatively to 45 patients and postoperatively to 59 patients. The mean (SD) age was 53.5 (16.5) years, and 51 (49%) patients were male. Patients underwent a broad range of surgery of mainly intermediate (55%) to major (33%) severity. The median minimal clinically important difference for DAH30 was 3 days; this was consistent across a broad range of scenarios, including earlier discharge home, complications delaying hospital discharge and the requirement for admission to a rehabilitation unit. Discharge home earlier than anticipated and discharge home rather than to a rehabilitation facility were both rated as important (median score = 5). Empirical data on the minimal clinically important difference for DAH30 may be useful to determine sample size and to guide the non‐inferiority margin for future clinical trials.